Das römische Recht und die Privatrechtsentwicklung in Ungarn im Mittelalter - Gábor Hamza (Journal on European History of Law)
The influence of Roman law in Hungarian legal education and development has been significant for centuries. Although formal reception of Roman law did not occur in Hungary, its impact can be observed in the development of legal terminology and the influence of Roman legal principles. The Romanization of Hungary, particularly during the Roman Empire's rule, left traces of Roman legal influence in the region. However, the continuity of Roman legal influence was disrupted by migrations and political factors. Despite this, the study of Roman law in Hungary gained momentum during the medieval period, especially through the education of Hungarian students in foreign universities. Attempts to codify and formally receive Roman law took place in the 15th and 16th centuries but were not fully realized. The Tripartitum, a work by István Werbőczy in the 16th century, consolidated customary Hungarian law and incorporated Roman legal terminology and principles. While the formal reception of Roman law did not occur in Hungary, its influence can be observed in legal practices and terminology throughout Hungarian legal history.